KARAKTER ARSITEKTUR TEPI SUNGAI DI KAMPUNG SASIRANGAN KOTA BANJARMASIN - Irwan Yudha Hadinata; Ira Mentayani (Universitas Lambung Mangkurat, 2018)
Banjarmasin as the city of a thousand rivers has become a region with strong riverside character. From its history, traditional kampungs grow along the riverbanks with unique features and characteristics. Along with the development of time and progress in all fields, the riverside kampung undergoes transformation that threatens the fading of the identity and existence of riverside architecture in Banjarmasin City. This study aims to identify the character of riverside architecture in Kampung Sasirangan and dwelling components that became the background of the character. The location of Kampung Sasirangan chosen based on the criteria of finding lanting houses, riverbank houses, titian, trunks, toilets, docks and bridges as part of the riverside architecture This research uses rationalistic method with typology as a classification analysis tool of mapping of residence typology and its physical component. The findings of this study illustrate the trend of changes and transformation of riverbanks and lanting houses in the area of Kampung Sasirangan that is happening and is real. These changes are generally not in the form of architectural form but in the material forming content and functions that exist in each of these houses. The strong influence of the road to the attraction of orientation and the changing factor of the community profession in Kampung Sasirangan, which is based on the main factor that is the economic accessibility that becomes the base of the changing factor of the area.